1999
DOI: 10.1038/10503
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of tumor-specific CD4+ T-cell tolerance to T-cell priming through in vivo ligation of CD40

Abstract: Tumor antigen-specific T-cell tolerance limits the efficacy of therapeutic cancer vaccines. Antigen-presenting cells mediate the induction of T-cell tolerance to self-antigens. We therefore assessed the fate of tumor-specific CD4+ T cells in tumor-bearing recipients after in vivo activation of antigen-presenting cells with antibodies against CD40. Such treatment not only preserved the responsiveness of this population, but resulted in their endogenous activation. Established tumors regressed in vaccinated mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
259
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(276 citation statements)
references
References 46 publications
13
259
1
3
Order By: Relevance
“…DCrestricted CD40 proficiency is necessary and sufficient to induce protective Th1 immunity, through IL-12 production, in a tumor vaccination setting [18]. Three seminal papers demonstrated that CD40 triggering in vivo by an agonist mAb can overcome CD4 1 and CD8 1 T-cell tolerance to tumor-associated antigens and induce tumor eradication [62][63][64]. We have shown that CD40 engagement by CD40L expressed by a tumor-cell vaccine can increase immunity against tumor antigens cross-presented by DCs [27] and that the CD40/CD40L axis is required for CTL induction by vaccination with GM-CSF/OX40L-transduced tumor cells [65].…”
Section: Discussionmentioning
confidence: 99%
“…DCrestricted CD40 proficiency is necessary and sufficient to induce protective Th1 immunity, through IL-12 production, in a tumor vaccination setting [18]. Three seminal papers demonstrated that CD40 triggering in vivo by an agonist mAb can overcome CD4 1 and CD8 1 T-cell tolerance to tumor-associated antigens and induce tumor eradication [62][63][64]. We have shown that CD40 engagement by CD40L expressed by a tumor-cell vaccine can increase immunity against tumor antigens cross-presented by DCs [27] and that the CD40/CD40L axis is required for CTL induction by vaccination with GM-CSF/OX40L-transduced tumor cells [65].…”
Section: Discussionmentioning
confidence: 99%
“…the antibody could provoke a productive immune response without subsequent immunization [8][9][10][11]. However, these previous studies have used an immunization protocol that gave a sustained Ag stimulus (peptide in IFA for example) [10,28].…”
Section: Cd40-cd154 Signalling Is Not Required For the Induction Of Tmentioning
confidence: 99%
“…These observations led to studies that have employed exogenous stimulation of this CD40-OX40 pathway with agonistic antibodies to prevent the induction of T cell tolerance. This can be done either at the surface of the APC (using anti-CD40) [8][9][10][11] or the surface of the T cell (using anti-OX40) [12,13]. Clearly the use of either approach to stimulate an immune response that is otherwise inadequate, or even one that might otherwise lead to tolerance (such as the poor immunogenicity of tumour Ag), can have potential therapeutic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have revealed that the state of activation and /or maturation of antigen-presenting cells ( APCs ) may determine whether T cells are primed or rendered tolerant. 6 CD40 is a member of the tumor necrosis factor ( TNF ) receptor family of cell surface proteins expressed on B cells, macrophages, and dendritic cells. It binds a CD40 ligand (CD40L /CD154 ), which is a member of the TNF superfamily expressed on activated T cells, basophils, and mast cells.…”
mentioning
confidence: 99%